A rapid stability charts analysis method for rock slopes based on Generalized Hoek-Brown criterion. Issue 1 (1st January 2021) - Wei, Yuan; Liyan, Wang; Xing, Zhai; hanhua, Tan; Shu, Peng; Yanyu, Xue; Wei, Wang; Xiaoyun, Sun; Jiandong, Niu
ABSTRACT: Stability charts for slopes remain useful in engineering practice because of their convenience and practicality. This paper presents a new stability chart analysis method based on the Generalized Hoek-Brown ( GHB ) criterion to rapidly calculate the factor of safety ( FOS ) of rock slopes. First, critical failure state charts ( CFSCs ) are produced to represent the relationships among the slope height, unit weight of the rock mass and all the parameters involved in the GHB criterion when the slopes lead to a critical failure state (i.e. FOS = 1.0). Second, based on the CFSCs, the formulas of the FOS derived from mi and dimensionless parameter σcmass / γ H are presented for slopes with different slope angles. Thus, the FOS for any slope with a GHB rock mass can be directly determined by taking the GHB parameters (i.e. σc, mi, GSI, and D ), the unit weight (γ) and the slope's geometrical parameters (i.e. height H and slope angle β ) as inputs. Finally, 25 cases selected from the published literature are used to illustrate the applicability and validity of the proposed method. The results for these cases show good agreement with those obtained with the limit equilibrium method ( LEM ).